KEMAMPUAN KOGNITIF SISWA DALAM MEMBACA TEKS EKONOMI KELAS XI- IPS K3 DI SMA NEGERI 10 MALANG - Riris Dwi Novianti; Mit Witjaksono; Agung Haryono (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2017)
Cognitive ability is a behavior that emphasizes the intellectual aspects, aswell as the knowledge, understanding, and the thinking of students inlearning. To measure the cognitive abilities of students using text reading,the study raced on Revised Bloom's Taxonomy. The purpose of this studywas to determine the level of students' cognitive abilities as measured bytests such as reading texts give the economy and about the description.This research uses a qualitative approach research with descriptivephenomenology. The subjects were students of class XI IPSK3 SMAN 10Malang totaling 29 students. Data collection techniques used in this studyinclude observation, testing, documentation and assessment rubrics.Meanwhile, data analysis includes data reduction, data presentation, andconclusion. Based on the survey results revealed that out of 29 studentswho take cognitive tests found 29 students who were able to reach a stageof cognitive ability at level C1, C2, and C3. Of the 29 students who takecognitive tests were seven students were able to achieve levels of C4 areanalyzed, four students on the test 1 that the reading